Modeling the thermal decomposition and residual mass of a carbon fiber epoxy matrix composite with a phenomenological approach: Effect of the reaction scheme. (22nd April 2021) - Langot, Jean; Chávez‐Gómez, Pablo; Lévesque, Martin; Robert, Etienne
Summary: The thermal decomposition of polymer matrix composites is a complex process involving hundreds of reactions and species, which are often modeled with simplified one‐step schemes. These schemes can be improved by adding intermediate reactions of different nature (competitive, parallel, and consecutive). However, the optimal number and nature of intermediate reactions are rarely discussed. In this paper, several reaction schemes of increasing complexity have been developed to model the decomposition of a carbon/epoxy composite. The kinetic parameters describing each reaction have been extracted from thermogravimetric analysis (TGA) by means of isoconversional methods. The composite mass loss rate and residual mass have been modeled and compared to TGA and tube furnace data. This research shows that adding parallel or consecutive intermediate reactions improves the agreement against TGA data compared to a single‐step model, but only competitive reactions can account for the variation of the residual mass observed in the tube furnace when the heating rate is varied.